Acquired Vulvar Lymphangioma Circumscriptum. (16th December 2013) - Uçmak, Derya; Aytekin, Sema; Sula, Bilal; Akkurt, Zeynep Meltem; Türkçü, Gül; Ağaçayak, Elif
Abstract : Lymphangioma circumscriptum (LC) is a benign dilation of lymph channels localized to the skin and subcutaneous tissues. It is generally localized in mouth mucosa, tongue, proximal regions of arms and legs, groin, axilla, and trunk. Primary vulvar involvement is very rare. Vulvar involvement occurs in various clinical settings. Here, two uncommon cases with giant lymphangioma circumscriptum mimicking genital warts will be presented: a 55-year-old female patient with extensive lymphangiectasic lesions and genital wart-like papular lesions in the vulva secondary to diffuse scrofuloderma scars and a 60-year-old female patient with verruca-like lesions secondary to chronic inflammation.